2017
DOI: 10.1093/femsre/fux020
|View full text |Cite
|
Sign up to set email alerts
|

Structure, function and regulation of Pseudomonas aeruginosa porins

Abstract: Pseudomonas aeruginosa is a Gram-negative bacterium belonging to the γ-proteobacteria. Like other members of the Pseudomonas genus, it is known for its metabolic versatility and its ability to colonize a wide range of ecological niches, such as rhizosphere, water environments and animal hosts, including humans where it can cause severe infections. Another particularity of P. aeruginosa is its high intrinsic resistance to antiseptics and antibiotics, which is partly due to its low outer membrane permeability. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
237
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 296 publications
(267 citation statements)
references
References 215 publications
6
237
0
4
Order By: Relevance
“…Figures 2C,D show that the KT2440 strains carrying the porin proteins boosted the hydrophobicity of the membrane by more than threefold in comparison to the parental and the mutant KT mscL strain. The OprF protein contributed the most to this process, as this is the major waterfilling porin in Pseudomonas (Chevalier et al, 2017). Consistent with the enhanced hydrophobicity of the cell's surface of the engineered KT2440 strains, changes in the uptake of N-phenyl-1-naphtylamina (NPN) were found, a suitable compound to assess the permeability barrier of the membrane (Helander and Mattila-Sandholm, 2000).…”
Section: Cell Growth and Membrane Assays Of The Engineered And Wild-tmentioning
confidence: 78%
See 1 more Smart Citation
“…Figures 2C,D show that the KT2440 strains carrying the porin proteins boosted the hydrophobicity of the membrane by more than threefold in comparison to the parental and the mutant KT mscL strain. The OprF protein contributed the most to this process, as this is the major waterfilling porin in Pseudomonas (Chevalier et al, 2017). Consistent with the enhanced hydrophobicity of the cell's surface of the engineered KT2440 strains, changes in the uptake of N-phenyl-1-naphtylamina (NPN) were found, a suitable compound to assess the permeability barrier of the membrane (Helander and Mattila-Sandholm, 2000).…”
Section: Cell Growth and Membrane Assays Of The Engineered And Wild-tmentioning
confidence: 78%
“…This pleiotropic trans-outer-membrane porin is to a large extent responsible for cell wall permeability and integrity and further contributes to the maintenance of the cell shape. Besides ion incorporation (weakly biased to cations), it is also responsible for the passage of low molecular mass sugars, toluene, and nitrate/nitrite (Chevalier et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…We used four different assays to assess the levels and activity of (1) pyocyanin, (2) elastase, (3) protease, and (4) rhamnolipids. Specific details for each assay are outlined below.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, it was shown that interferon-γ led to the induction of the Pseudomonas aeruginosa lectin PA-I via activation of the quorum-sensing network that is required for the production of virulence factors [29]. Noticeably, this effect was shown to be triggered by direct binding of interferon-γ on OprF [29], which is a multifunctional outer membrane porin [30] that is required for P. aeruginosa virulence regulation [31] and involved in regulation of biofilm formation [32]. It has also been observed that dynorphin A, an endogenous opioid, modifies P. aeruginosa physiology [33].…”
Section: Introductionmentioning
confidence: 99%